1986
DOI: 10.1111/j.1432-1033.1986.tb09912.x
|View full text |Cite
|
Sign up to set email alerts
|

Multispecific DNA methyltransferases from Bacillus subtilis phages

Abstract: Temperate Bacillus subtilis phages SPR, q3T, e l l and SPB code for DNA methyltransferases, each having multiple sequence specificities. The SPR wild-type and various mutant methyltransferases were overproduced 1 000-fold in Escherichia coli and were purified by three consecutive chromatographic steps.The stable form of these multispecific enzymes in solution are monomers with a relative molecular mass (M,) of about 50000. The methyl-transfer kinetics of the SPR wild-type and mutant enzymes were determined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In order to activate the chimeric enzyme, we introduced amino acid exchanges, insertions and deletions into TRD EF, to assimilate its sequence stepwise to the corresponding sequence of TRD E (Figure 4). For an analysis of the DNA methylation capacities of the resulting mutant derivatives of M.SPR-EF (M.SPR-EF-1 to -EF-8) we tested the in vitro methylation activity of Escherichia coli cells overexpressing the different mutant proteins as described previously (Gunthert et al, 1986). These analyses revealed that alterations of amino acids within regions I and II or in both regions (M.SPR-EF-1-4) had no activating effect.…”
Section: Fe and Efmentioning
confidence: 99%
“…In order to activate the chimeric enzyme, we introduced amino acid exchanges, insertions and deletions into TRD EF, to assimilate its sequence stepwise to the corresponding sequence of TRD E (Figure 4). For an analysis of the DNA methylation capacities of the resulting mutant derivatives of M.SPR-EF (M.SPR-EF-1 to -EF-8) we tested the in vitro methylation activity of Escherichia coli cells overexpressing the different mutant proteins as described previously (Gunthert et al, 1986). These analyses revealed that alterations of amino acids within regions I and II or in both regions (M.SPR-EF-1-4) had no activating effect.…”
Section: Fe and Efmentioning
confidence: 99%
“…The Mcr A Dcm A E. coli strain GM2929 (Palmer and Marinus 1994) was used to check the phenotype of hybrids containing TRD E. Plasmid pKB131 (Gunthert et al 1981(Gunthert et al , 1986aBuhk et al 1984;Posfai et al 1984) kindly provided by Dr. T. Trautner, carries the gene for the SPR DNA methylase and is a derivative of pBR328. Plasmid pTrc99-SPRMT was generated by moving the sprM gene into pTrc99A (Gunthert et al 1986b;Balganesh et al 1987;Trautner et al 1988a, b;Wilke et al 1988).…”
Section: Bacterial Strains and Plasmid Constructsmentioning
confidence: 99%
“…In both 5mC and amino methylases, the largest variable region lies immediately downstream of conserved motif VIII and contains one or more Target Recognizing Domains (TRDs) responsible for DNA sequence speci®city (Gunthert et al 1986a;Wilke et al 1988;Lauster et al 1989;Klimasauskas et al 1991;Mi and Roberts 1992). When individual TRDs were identi®ed and their boundaries de®ned by determining the eects of mutations and chimeric constructs, multispeci®c methylases were found to have as many as ®ve active TRDs Trautner et al 1988a, b;Wilke et al 1988), while monospeci®c methylases appeared to have just one (Klimasauskas et al 1991;Kumar et al 1992;Mi and Roberts 1992).…”
Section: Introductionmentioning
confidence: 97%